Update on the Treatment of Diabetic Retinopathy - Jennifer L. Wilkinson-Berka; Antonia G. Miller (The Scientific World Journal)
Retinopathy is the most feared complication of diabetes, compromising quality of life in most sufferers. Almost all patients with type 1 diabetes will develop retinopathy over a 15- to 20-year period, and approximately 20–30% will advance to the blinding stage of the disease[1]. Greater than 60% of patients with type 2 diabetes will have retinopathy. This situation is highlighted by the frightening statistic that diabetic retinopathy (DR) remains the most common cause of vision impairment in people of working age in Western society. With the global epidemic of type 2 diabetes, this predicament is set to worsen as over 360 million people are projected to suffer from diabetes and its complications by 2030. Vision loss from diabetes is due to a number of factors, including haemorrhage from new and poorly formed blood vessels, retinal detachment due to contraction of deposited fibrous tissue, and neovascular glaucoma resulting in an increase in intraocular pressure. Diabetic macular oedema is now the principal cause of vision loss in diabetes and involves leakage from a disrupted blood-retinal barrier. In terms of treatment, there is clear evidence that strict metabolic and blood pressure control can lower the risk of developing DR and reduce disease progression. Laser photocoagulation and vitrectomy are effective in preventing severe vision loss in DR, particularly in the most advanced stages of the disease. However, both procedures have limitations. This review examines evidence from preclinical and clinical studies that shows that targeting inhibition of the renin-angiotensin system, vascular endothelial growth factor, corticosteroids, protein kinase C, growth hormone, and advanced glycation end-products are potential treatments for DR.